2022
DOI: 10.1007/s10552-022-01662-y
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccination coverage and factors among American Indians in Cherokee Nation

Abstract: Purpose We estimated human papillomavirus (HPV) vaccine initiation coverage among American Indian adolescents and identified factors associated with HPV vaccination among parents of these adolescents. Methods We developed, tested, and disseminated a survey to a random sample of 2,000 parents of American Indian adolescents aged 9–17 years who had accessed Cherokee Nation Health Services from January 2019 to August 2020. We used log-binomial regression to estimate the una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The results of this study indicate that the reason parents are intentioned to vaccinate was to avoid their child's cancer in the future and to participate in the school program, this is in line with the results of other researchers who found the most common reason reported by parents to vaccinate their children is to protect them from cancerrelated to HPV and to get recommendations from healthcare providers (10). This reason is the most important thing for parents because they don't want their children to get cervical cancer in the future.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study indicate that the reason parents are intentioned to vaccinate was to avoid their child's cancer in the future and to participate in the school program, this is in line with the results of other researchers who found the most common reason reported by parents to vaccinate their children is to protect them from cancerrelated to HPV and to get recommendations from healthcare providers (10). This reason is the most important thing for parents because they don't want their children to get cervical cancer in the future.…”
Section: Discussionsupporting
confidence: 90%
“…The main reason described by parents for HPV vaccination was preventing cancer in their children. This finding of cancer prevention being the most compelling reason for HPV vaccination was also reported in a survey of Cherokee Nation parents [ 16 ] and in a national study of over 1000 parents [ 17 ]. Our finding that parental concerns about safety being a major barrier to HPV vaccination is also consistent with the findings from a systematic review among American Indian and Alaska Native persons [ 18 ] and reviews among other US populations [ 19 21 ].…”
Section: Discussionsupporting
confidence: 67%
“…It is well understood that lack of information contributes to vaccine reluctance, with many studies suggesting that increasing awareness of HPV, its vaccine and its association with cancer can contribute to better vaccine uptake and infection prevention [ 18 , 21 , 23 , 24 , 25 , 26 , 27 ]. A study involving American Indian adolescents found that HPV vaccine initiation was higher among those whose parents were aware of the vaccine and had received a recommendation from their medical practitioner for their child to receive it [ 28 ]. Researchers have suggested that Indigenous participants have “little” knowledge about HPV, its mode of transmission, the HPV vaccine or its oncogenic potential [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study involving American Indian adolescents found that HPV vaccine initiation was higher among those whose parents were aware of the vaccine and had received a recommendation from their medical practitioner for their child to receive it [ 28 ]. Researchers have suggested that Indigenous participants have “little” knowledge about HPV, its mode of transmission, the HPV vaccine or its oncogenic potential [ 28 ]. However, there was no evidence quantifying knowledge of HPV, its vaccine and related cancers among Indigenous Australians, or the individual factors associated with poorer knowledge.…”
Section: Introductionmentioning
confidence: 99%